Application of bio-silicic acid to improve yield and fertilizer efficiency of paddy on tidal swamp land - Donny Nugroho KALBUADI; Laksmita Prima SANTI; Didiek Hadjar GOENADI; Junita BARUS (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2020)
The soils in tidal swamp land as new development area for rice in Indonesia have a considerably low available silica (Si) because very acid condition and no Si fertilization. Therefore, increasing the productivity of rice as Si accumulator plant, in tidal swamp land requires silica fertilizer. This research presented the effect of applications of silicon in the form of orthosilicic acid (H4SiO4) enriched with selected Sisolubilizing fungi, formulated as 4-gram tableted Si fertilizer (BioSilAc) on tidal swamp land soil to improve yield and reduce chemical fertilizer dosage for rice. Field experiment was conducted in Ketapang subdistrict, South Lampung by using a Randomized Block Design (RBD) with six treatments and four replicates. The treatments consisted of (ha-1 season-1): 100% NPK recommended dosage (P1); 100% NPK + 80 BioSilAc tablets (P2); 75% NPK + 80 BioSilAc tablets (P3); 75% NPK + 100 BioSilAc tablets (P4); 50% NPK + 120 BioSilAc tablets (P5); and control (P6). The results showed that P2 treatment increased the highest rice yield in dried harvested grain by 7.6% or equivalent to 500 kg ha-1 compared to P1 treatment. The highest fertilization efficiency can be achieved in P4 treatment which means the NPK recommended dosage can be reduced 25% by adding 100 BioSilAc tablets ha-1 season-1 indicated by insignificantly different productivity compared to that of P1. The Revenue/Cost (R/C) values showed that P2 treatment was economically feasible fertilization practices.